Two-Stage Sampling from a Prediction Point of View - Jan F. Bjørnstad; Elinor Ytterstad (Statistics Norway, Research Department, 2004)
This paper considers the problem of estimating the population total in two-stage cluster sampling when cluster sizes are unknown, making use of a population model arising basically from a variance component model. The problem can be considered as one of predicting the unobserved part Z of the total, and the concept of predictive likelihood is studied. Prediction intervals and a predictor for the population total are derived for the normal case, based on predictive likelihood. The predictor obtained from the predictive likelihood is shown to be approximately uniformly optimal for large sample size and large number of clusters, in the sense of uniformly minimizing the mean square error in a partially linear class of model-unbiased predictors. Three prediction intervals for Z based on three similar predictive likelihoods are studied. For a small number n0 of sampled clusters they differ significantly, however, for large n0 the three intervals are practically identical. Model-based and design-based coverage properties of the prediction intervals are studied based on a comprehensive simulation study. Roughly, the simulation study indicates that for large sample sizes the coverage measures achieve approximately the nominal level 1 - á and are slightly less than 1 - á for moderately large sample sizes. For small sample sizes the coverage measures are about 95% of the nominal level.
Keywords: C42; C13; C15; 330; Survey sampling; population model; predictive likelihood; optimal predictor; prediction intervals; simulation